CLINICAL AND MORPHOLOGICAL ANALYSIS OF A PULMONARY ALVEOLAR PROTEINOSIS CASE IN AN INFANT - Starchenko, I.I.; Fylenko, B.M.; Roiko, N.V.; Vakhnenko, A.V.; Rumiantseva, M.A.; Dyachenko, L.V. (World of Medicine and Biology, 2025)
This paper presents a clinical case of undiagnosed pulmonary alveolar proteinosis in a 43-day-old child, verified pathomorphologically, including a detailed clinico-morphological analysis. Due to diverse etiopathogenetic mechanisms and non-specific clinical manifestations – specifically, progressive respiratory failure mimicking treatment-resistant interstitial pneumonia – pulmonary alveolar proteinosis remains a significant diagnostic challenge. Early detection is crucial for effective treatment and prognosis. The stages of differential diagnosis, based on the dynamics of clinico-laboratory and instrumental changes, are highlighted. Key diagnostic steps included radiographic detection of bilateral lung opacification without clear focal points and echocardiographic confirmation of severe pulmonary hypertension. A distinctive feature of this case was the paradoxical clinical presentation: the absence of fever and a negative SARS-CoV-2 antigen test despite the mother having moderate COVID-19 at 31–32 weeks of gestation, indicating profound immune reactivity. It was established that the cause of secondary PAP in this child was an immunodeficiency syndrome associated with thymus pathology. The immunodeficiency manifested as a deficiency of cells across all major lymphocyte subpopulations and reduced neutrophil phagocytic activity. Despite intensive therapy, the case was fatal on the 19th day of hospitalization. Pathomorphologically, the diagnosis was confirmed by the presence of PAS-positive eosinophilic material within the alveoli and grade V thymus atrophy.
Keywords: immunodeficiency; etiology; differential diagnosis; pathomorphology; thymus atrophy; pulmonary alveolar proteinosis